PENGARUH GOOD CORPORATE GOVERNANCE DAN REGULASI PEMERINTAH TERHADAP PENGUNGKAPAN INFORMASI AKUNTANSI LINGKUNGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2016-2019) - Intan Wahyuningsih; Wahyu Meiranto (Diponegoro Journal of Accounting, 2021)
The purpose of this research is to exemine the effect of good corporate governance and government regulation on the environmental accounting information disclosure. Variabel used in the examination are board gender diversity, environmental committee delegation, institutional ownership, foreign ownership and government regulation as the independent variabel and environmental accounting information disclosure as the dependent variabel. The population of this study is manufacturing companies listed in Indonesia Stock Exchange (IDX) during the 2016-2019. Sampling based on purposive sampling method with 72 total sample. Data analysis was performed classical asumption and hypothesis testing using linear regression. The result of this study indicates that the directors gender diversity and foreign ownership have positive and negatif significant effect on environmental accounting information disclosure. Meanwhile, environmental committee delegation and government regulation have positive and insignificant on environmental accounting information disclosure. Whereas, institutional ownership has a negatif and insignificant effect on environmental accounting information disclosure.